STRUKTUR ALUR DAN BENTUK KONFLIK YANG MEMBANGUN NOVEL SAMAN KARYA AYU UTAMI - Turistiani, Trinil (Jurnal Pena Indonesia, 2017)
In the novel Saman, it can be found some interesting problems to be analyzed. This paper limits the descriptive analysis of flow and conflict structures and their interrelationships in the meaning of novel. The problem is considered interesting because the path created by the author is not sequential. In addition, the flow in the novel is also interesting because it is different from the conventional rules flow. Saman is a fragment of Ayu Utami's first novel, Laila Tak Mampir di New York. This Fragment won the Jakarta Arts Council Roman contest 1999 and also the recipient of the award for his work which is considered to expand the limit of writing in the community. The structure of Saman's novel flow is not based on the order of life events (in fact). It is intended by the author to have the reader interested in reading the entire contents of the novel. The meaning to be conveyed is to commit the wrong action (affair, leave the duties of priesthood) will lead to other people hurt and will lead to conflict or problems. The form of conflict that built the flow of novel Saman there are two, namely social conflict and inner conflict. Both forms of this conflict arise because this novel raises the problem of infidelity and sexual problems.